Revisiting Teacher Support and Psychological Well-Being among Santri in Pesantren: An Explanatory Analysis - Ezadany, Adellia; Khusumadewi, Ari (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Santri psychological well-being is an important aspect of pesantren (Islamic boarding school) education, as it supports students’ adaptation, emotional stability, and engagement in daily activities. Teacher support is often considered a key factor in shaping positive psychological outcomes in educational settings. However, empirical evidence within the pesantren context remains limited. This study examines whether teacher support has a measurable effect on santri psychological well-being at Alif Laam Miim Islamic Boarding School, Surabaya. This study employed a quantitative approach using an explanatory survey design involving 118 santri selected through a census sampling technique. Data were collected using Likert-scale questionnaires measuring teacher support and psychological well-being. The instruments demonstrated acceptable internal consistency. Data analysis was conducted using simple linear regression following classical assumption testing. The results indicate that teacher support has a positive but statistically non-significant relationship with psychological well-being (p = 0.535 > 0.05). The coefficient of determination (R² = 0.003) and the negative adjusted R² value suggest that teacher support provides minimal explanatory value within the model. These findings indicate that teacher support does not have a measurable effect on santri psychological well-being in this context. The study highlights the importance of considering psychological well-being in pesantren as a multidimensional construct shaped by a combination of internal and external factors, including personal resilience, peer relationships, and institutional context.